Implementasi Teori Humanistik Carl Rogers dalam Meningkatkan Kemampuan Berpikir Kritis Siswa MTsN 1 Lebong - Meza Tiara; Asri Hajar Dewanti; Debi Irama; Hendra Harmi; Mirzon Daheri (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
The application of humanistic theory in learning has proven effective in increasing students' self-confidence and involvement. This theory emphasizes understanding, empathy and respect for students' individual needs, thereby creating a comfortable learning atmosphere and encouraging students' courage to express opinions and participate actively. In addition, this approach has a positive impact on students' critical thinking abilities, which can be seen from improving analytical skills, decision making and problem solving abilities. This research uses a qualitative approach with descriptive and experimental methods. Data was obtained through interviews, class observations, and documentation. The research subjects were class VIII students at MTs N 1 Lebong, using purposive and random sampling techniques to determine the sample. Data analysis was carried out thematically to evaluate the application of Carl Rogers' humanistic theory and its impact on students' critical thinking. The research results show that despite challenges, such as time constraints and differences in student abilities, the humanistic approach provides significant benefits. Teachers are advised to be more creative in adapting this method to students' needs so that optimal results can be achieved.